Penilaian belajar siswa di sekolah / Herman Yosep Sunu Endrayanto, Yustiana Wahyu Harumurti ; editor, C. Erni Setiyowati, Yosef Bayu Anangga - HERMAN YOSEP SUNU ENDRAYANTO , 1975-; Yustiana Wahyu Harumurti; Erni Setiyowati, C.; Yosef Bayu Anangga (Kanisius, 2014)
334 hlm. : ilus. ; 23 cm.